2020
DOI: 10.1007/s00586-020-06491-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of operative timing on the early post-operative radiological and clinical outcome after kyphoplasty

Abstract: Purpose To clarify the relationship between operative timing and the early post-operative radiological and clinical outcome after kyphoplasty. Methods We conducted a retrospective cohort study including patients who underwent kyphoplasty of a single vertebra. Patients were divided into three groups (acute [< 2 weeks], subacute [2–6 weeks] or chronic [6–51 weeks]) based on the interval between fracture and surgery. The relative ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The duration between the patients' admission and the treatment decision was 4 ± 4 days (range: 0-26, median 2 days) and did not differ depending on surgical or conservative therapy choice (P = .376). At the day of treatment decision the mean OF-score was 8.2 ± 1.7 (range [4][5][6][7][8][9][10][11][12] and differed between conservative (7.6 ± 1.8) and surgical treated patients (8.4 ± 1.7, P = .029). Thereby a total of 15 patients were treated conservatively despite an OF score of more than 6 and 7 patients were treated surgically despite an OF score of less than 6.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The duration between the patients' admission and the treatment decision was 4 ± 4 days (range: 0-26, median 2 days) and did not differ depending on surgical or conservative therapy choice (P = .376). At the day of treatment decision the mean OF-score was 8.2 ± 1.7 (range [4][5][6][7][8][9][10][11][12] and differed between conservative (7.6 ± 1.8) and surgical treated patients (8.4 ± 1.7, P = .029). Thereby a total of 15 patients were treated conservatively despite an OF score of more than 6 and 7 patients were treated surgically despite an OF score of less than 6.…”
Section: Resultsmentioning
confidence: 97%
“…Taking the recent literature into account stand-alone cement augmentation seems to be justified. Palmowski et al 4,12 reported of favorable clinical and radiological results with reduction potential and low reduction loss in the short run. Similarly, Gu et al 3 reported similar clinical results after both stand-alone kyphoplasty and hybrid stabilization.…”
Section: Limitationsmentioning
confidence: 99%
“…Posterior stabilization was recommended in unstable fractures, such as OF type 3-5 fractures, depending on the clinical course. To date, several studies have evaluated the treatment of OVCFs using the OF score [2,[9][10][11][12], including the treatment of short-and long-segmental posterior stabilizations. Recently, OF classifications have gained an increased level of acceptance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%